2022
DOI: 10.1038/s41598-022-05401-w
|View full text |Cite
|
Sign up to set email alerts
|

The influence of myofascial release on pain and selected indicators of flat foot in adults: a controlled randomized trial

Abstract: Flat foot pain is a common complaint that requires therapeutic intervention. Currently, myofascial release techniques are often used in the therapy of musculoskeletal disorders. A group of 60 people suffering from flat feet with associated pain. Patients were assigned to four groups (15 people each): MF—myofascial release, E—the exercise program, MFE—myofascial release and the exercise program, C—no intervention. The rehabilitation program lasted 4 weeks. The NRS scale was used to examine pain intensity and Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In contrast, dynamic tests showed statistically significant changes for indicators, particularly in groups assigned to the treatment protocol. The MF group exhibited the most changes in dynamic testing to assess the entire foot in the support phase, whereas the MFE group showed significant changes in selected subphases [15][16] .…”
Section: Estimating the Effects Of Mfrt On Foot Function Indexmentioning
confidence: 99%
“…In contrast, dynamic tests showed statistically significant changes for indicators, particularly in groups assigned to the treatment protocol. The MF group exhibited the most changes in dynamic testing to assess the entire foot in the support phase, whereas the MFE group showed significant changes in selected subphases [15][16] .…”
Section: Estimating the Effects Of Mfrt On Foot Function Indexmentioning
confidence: 99%
“…A therapeutic program has been implemented to strengthen the muscles of the legs, the aim of which is to get rid of the pain that accompanies performance and to develop swimming kinematics. The recovery procedures include five phases, as follows : -Myofascial release, in which six sessions were performed, aimed at eliminating cramps in the feet and returning the foot to its normal state (Bac et al, 2022;Brandl et al, 2021) -Stretching Where the flexibility of the lower extremity, especially the feet, is one of the important and influencing factors in the performance of the swimmer, and the flexibility of the feet is very effective, especially in the strikes of the legs under water . (Shen et al, 2022;Shimojo et al, 2019a) -Shockwave Studies indicate (Hayano et al, 2021;Tognolo et al, 2022;van Doormaal et al, 2020) To the importance of shockwave in improving performance of swimmers, as studies have confirmed that shockwave works to get rid of the pain of the two legs and return the foot to normal after injury or excessive stress.…”
Section: Experimental Protocolmentioning
confidence: 99%